GLOBAL REVIEW OF FINANCIAL THE RMOMETER PRACTICES: THE LEAN ACCOUNTING - Muhammad Zia ur Rehman,; Sadaf Razzaq,; Sara Shafaqat,; Sajjad Ahmad Baig, (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
New accounting concepts has been designed to reflect the financial performance of lean enterprises in a better way. This paper is a systematic review of Lean Accounting articles that published since 2000 to 2020 around the globe. This review study on the literature of Lean accounting proceeds from the following search engine: i.e. Emerald insights and google scholar. Because modern era is providing a roadmap for finance managers while seeking to transit their organizations to Lean enterprises. Due to the significant financial impacts of lean practices a very little consideration was given to change the accounting systems which support the new production methods. Most of the companies introducing Lean thinking realize that their finance and accounting systems are very wasteful and ineffective. This review study aims to determine that howfactors influence the adoption of lean accounting by lean-manufacturing companies.